Strategy for generation of replication–competent recombinant rotaviruses expressing multiple foreign genes. (12th April 2021) - Hatazawa, Riona; Fukuda, Saori; Kumamoto, Kanako; Matsushita, Fumio; Nagao, Shizuko; Murata, Takayuki; Taniguchi, Koki; Matsui, Taei; Komoto, Satoshi
Abstract : With the recent establishment of robust reverse genetics systems for rotavirus, rotavirus is being developed as a vector to express foreign genes. However, insertion of larger sequences such as those encoding multiple foreign genes into the rotavirus genome has been challenging because the virus segments are small. In this paper, we attempted to insert multiple foreign genes into a single gene segment of rotavirus to determine whether it can efficiently express multiple exogenous genes from its genome. At first, we engineered a truncated NSP1 segment platform lacking most of the NSP1 open reading frame and including a self-cleaving 2A sequence (2A), which made it possible to generate a recombinant rotavirus stably expressing NanoLuc (Nluc) luciferase as a model foreign gene. Based on this approach, we then demonstrated the generation of a replication-competent recombinant rotavirus expressing three reporter genes (Nluc, EGFP, and mCherry) by separating them with self-cleaving 2As, indicating the capacity of rotaviruses as to the insertion of multiple foreign genes. Importantly, the inserted multiple foreign genes remained genetically stable during serial passages in cell culture, indicating the potential of rotaviruses as attractive expression vectors. The strategy described here will serve as a model for the generation of rotavirus-based vectors designed for the expression and/or delivery of multiple foreign genes.